(untitled) (Літератури світу: поетика, ментальність і духовність, 2015)
The article is devoted to creativity of A. I. Kuprin. In particular, the example of the story «Sulamif» reveals the image of the inner world of the author. The article deals with the creative development of the person, particulars of true love, features of inner and exterior beauty, mentality of the author, the image of the inner world of a creative personality.